Changing Patterns of Salmonella enterica Serovar Rissen From Humans, Food Animals, and Animal-Derived Foods in China, 1995–2019 - Elbediwi, Mohammed; Shi, Daiwei; Biswas, Silpak; Xu, Xuebin; Yue, Min (Frontiers in Microbiology, 2021)
Salmonellosis represents a growing threat to global public health. Salmonella enterica remains the leading cause of bacterial foodborne diseases in China. Salmonella enterica serovar Rissen (S. Rissen) has been recognized as one of the emerging serovars among humans in numerous countries worldwide. However, the prevalence of S. Rissen in China is largely lacking. To address essential epidemiological information for S. Rissen in China, a total of 1,182 S. Rissen isolates recovered from samples across the food chain were collected from 16 provinces or province-level cities between 1995 and 2019. Risk factors due to the consumption of animal-derived food products were also analyzed. We found S. Rissen is widely distributed, especially in the Eastern and Southern parts of China, and there is an increasing frequency in recent years as evidenced by the greater number of isolates recovered in 2016, 2017, and 2018. Interestingly, the majority of S. Rissen isolates recovered in this study were from human samples (63.4%; 749/1182), remarkably, 58.4% )438/749) were from asymptomatic carriers. We obtained most of the S. Rissen isolates from humans from Guangxi (59.5%; 446/749) and Shanghai (29.5%; 221/749). Among 302 human diarrheal isolates (40.3%; 302/749), we found 44.6 % (139/311) of S. Rissen in children with diarrhea (age below 10 years old). This is of clinical significance as diarrhea is one of the crucial causes of child mortality globally and our findings here highlighted the importance of Salmonella infections in Chinese children. Additionally, S. Rissen isolates were also found to be associated with pork and poultry products in China. This study projected the most updated national-wide study of S. Rissen isolates obtained from different sources in China over the past two decades. Continued surveillance is warranted to further monitor this emerging serovar in China and elsewhere over the world.